2017
DOI: 10.15252/emmm.201708450
|View full text |Cite
|
Sign up to set email alerts
|

Thrombopoietin: tickling the HSC's fancy

Abstract: Thrombopoietin (THPO) has been well characterized as a key regulator of platelet production. THPO also plays an important role in the maintenance and regulation of hematopoietic stem cells (HSCs). In this issue of EMBO Molecular Medicine, Pecci et al (2018) describe a newly identified homozygous mutation in THPO causing congenital amegakaryocytic thrombocytopenia, a disease characterized by a significant impairment in platelet production with rapid onset of aplastic anemia within a few years. The paper nicely … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“… 43 In contrast, in a number of murine tumor models, irradiation induced an immunosuppressive macrophage phenotype. 27–29 44 In these models, macrophages inhibited T-cell activation. Our findings suggest that irradiation repolarizes macrophages to a Th1-oriented phenotype which not just directly promotes pro-inflammatory macrophages but may be able to facilitate anticancer function indirectly via activating T cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 43 In contrast, in a number of murine tumor models, irradiation induced an immunosuppressive macrophage phenotype. 27–29 44 In these models, macrophages inhibited T-cell activation. Our findings suggest that irradiation repolarizes macrophages to a Th1-oriented phenotype which not just directly promotes pro-inflammatory macrophages but may be able to facilitate anticancer function indirectly via activating T cells.…”
Section: Discussionmentioning
confidence: 99%
“… 26 Other studies suggested that irradiation of tumors was associated with a more immunosuppressive phenotype of TAM. 27–29 Jones et al found that the depletion of macrophages by an anti-CSF antibody greatly increased tumor ablation upon irradiation (10 Gy) in murine tumors generated from a colorectal and a pancreatic cell line. Obviously, the effect of irradiation appears to depend on the model, irradiation dose, tissue as well as on the investigated time point after irradiation.…”
Section: Introductionmentioning
confidence: 99%
“…In our experiment, we used AICAR as a positive control. AICAR, which is an AMPK activator, has been reported as able to recover muscle wasting induced by inflammation [ 22 ]. AICAR was intraperitoneally injected at 250 mg/kg every 2 days.…”
Section: Methodsmentioning
confidence: 99%
“…Sequencing and follow-up functional assays in a family with three affected members found a previously unknown homozygous mutation in the THPO gene. 9,10 The authors showed that it was disease causing, resulting in impaired secretion of the thrombopoietin hormone. They were able to successfully treat the three patients with romiplostim, a recombinant thrombopoietin receptor agonist.…”
Section: Resultsmentioning
confidence: 99%